Inequality of opportunity theory and measurement (Bingley, U.K. : Emerald, 2011)
Research on Economic Inequality, Volume 19, Inequality of Opportunity contains eight papers, both theoretical and applied, on the concept of equality of opportunity which says that a society should guarantee its members equal access to advantage regardless of their circumstances, while holding them responsible for turning that access into actual advantage by the application of effort. Theoretical papers discuss to what extent some of the measures of inequality of opportunity meet the reward and the compensation principles, a new methodology for evaluating long-term income distributions according to the equality of opportunity principle, the implications of partial observability of individuals circumstances on the measurement of inequality of opportunity and the advantages of applying segregation indices to study inequality in life chances when the variable is ordinal. The applied work includes studies that investigate how governments affect inequality of opportunity through the design of their tax and transfer schemes in 15 European countries, the changing role of circumstances for measuring inequality of opportunity in Chile, the existence of a poverty trap in Haiti and its consequences for equality of opportunity, and the importance of the correlation between circumstances and effort in the measurement of inequality of opportunity in U.S. during the period 1969-2007.
ch. 1. Compensation, reward, and the measurement of unfair inequalities / Paolo Brunori, Vito Peragine -- ch. 2. The implication of partial observability of circumstances on the measurement of IOp / Patrizia Luongo -- ch. 3. Mobility and long-term equality of opportunity / Flaviana Palmisano -- ch. 4. Measuring inequality in life chances with ordinal variables / Jacques Silber, Gaston Yalonetzky -- ch. 5. Equality of opportunity and redistribution in Europe / Lina Dunnzlaff, Dirk Neumann, Judith Niehues, Andreas Peichl -- ch. 6. Measuring circumstances : Francs or Ranks, does it matter? / Arnaud Lefranc, Nicolas Pistolesi, Alain Trannoy -- ch. 7. Changes over time in parental education and inequality of opportunities in Chile / Andrea B{u2865}z-Montenegro, Juan Prieto-Rodruez, Rafael Salas -- ch. 8. Vulnerability to poverty : a microeconometric approach and application to the Republic of Haiti / Evans Jadotte -- ch. 9. Inequality of opportunity in the United States : trends and decomposition / Gustavo A. Marrero, Juan G. Rodruez.
Keywords: Income distribution; Economics